19 Myocardial perfusion mapping in cardiac amyloidosis- unearthing the spectrum from infiltration to ischaemia. (March 2019) - Kotecha, Tushar; Martinez-Naharro, Ana; Brown, James; Little, Callum; Knight, Daniel; Steriotis, Alexandros; Patel, Niket; Rakhit, Roby; Hawkins, Philip; Gillmore, Julian; Moon, James; Xue, Hui; et al.
Abstract : Background: Cardiac involvement is the main driver of outcome in systemic amyloidosis, but the relationship between amyloid deposits and outcomes is not well understood. The simple explanation of physical, mechanical replacement of the interstitium by amyloid seems insufficient. Preliminary studies support the hypothesis that myocardial ischaemia could contribute to cell damage. Purpose: (1) To assess myocardial ischaemia in cardiac amyloidosis. (2) To compare patients with cardiac amyloidosis to patients assessed on invasive coronary angiography (ICA) to have normal coronary physiology (NCP), microvascular dysfunction (MVD) and triple vessel coronary disease (3VD). (3) To assess correlation of perfusion mapping to markers of disease severity and prognosis. Methods: 86 patients and 20 healthy volunteers (HV) underwent CMR at 1.5T (Siemens) with standard cine, PSIR-LGE, T1, T2, Extracellular Volume (ECV) mapping and adenosine stress with myocardial blood flow (MBF) mapping. Thirty-eight patients also underwent ICA with 3 vessel assessment of Index of Microcirculatory Resistance and Fractional Flow Reserve: 7 had cardiac amyloidosis, 8 had NCP, 15 had MVD and 8 had 3VD. Results: Cardiac amyloidosis patients had severe reduction in stress MBF and myocardial perfusion reserve (MPR) (1.22 ml/g/min±0.70 and 1.62±0.63) compared to HV (3.21 ml/g/min±0.64, p<0.001 and 4.17±0.78, p<0.001), NCP (2.66±0.56, p<0.001 and 2.51±0.43, p=0.036) and MVD (2.10±0.31, p<0.001 and 2.29±0.87, p=0.014) with the degree of reduction being similar only to patients with 3VD (1.44±0.54, p=1.000 and 1.64±0.68, p=1.000) (figure 1 ). Rest MBF was also lower in amyloidosis than HV. Cardiac amyloidosis stress MBF and MPR inversely correlated with amyloid burden (ECV, r=−0.715, p<0.001, transmurality of LGE, p<0.01), systolic dysfunction (EF, r=0.405, p<0.01), and blood biomarkers (NT-proBNP (r=−0.678, p<0.001) and Troponin T (r=−0.628, p<0.001)). There was a correlation between stress MBF and native T1 (r=−0.588, p<0.001) but not T2 (p=0.591). Stress MBF and MPR were early disease markers, being elevated in patients with early cardiac amyloid infiltration (raised ECV, no LGE, p<0.01 vsHV). Conclusion: Myocardial ischaemia is common in cardiac amyloidosis – with stress MBF and MPR similar to that of patients with 3VD. The reduction correlates with the degree of amyloid infiltration and markers of adverse prognosis, highlighting the potential role of myocardial ischaemia as a key mechanism in the pathophysiology of cardiac amyloidosis.